Does broad gender diversity affect corporate social responsibility disclosures? - Jean Stevany Matitaputty; Arthik Davianti (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
Nowadays, corporate social responsibility (CSR) disclosures becoming a business world issue. Many public listed companies are voluntarily disclosing their CSR information. This study aims to examine the relationship between gender diversity and CSR disclosures in basic and chemical manufacturing companies listed on the Indonesian stock exchange during 2014 to 2016 periods. The analysis method used in this research was a mixed-method, a combination of quantitative and qualitative analysis techniques. The quantitative analysis implemented in the study by utilizing the Spearman correlation. Further, qualitative analysis was based on content analysis. The results of this study showed that there is a lack of gender diversity amongst board members since the number of women on the boards in basic and chemical manufacturing companies still being a minority. Therefore, the relationship between gender diversity as measured by the level of female on the company board and CSR disclosures were insignificant.